1982
DOI: 10.1021/jo00147a018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-15 NMR spectroscopy: prototropic tautomerism of azoles

Abstract: 9-[l-(Methylthio)ethylidene]bicyclo[4.2.1]nonane (41).This compound is prepared and isolated as described for 15; yield 68%. Extremely pure product was obtained with the aid of high-performance LC (hexane): MS, m/e 196; 1H NMR (CDC13) 3.30 (m, 1), 3.03 (m, 1), 2.20 (s, 3), 1.97 (s, 3), 2.0-1.2 (m, 12). syn -9-Acetyl-9-chlorobicyclo[4.2.1]nona-2,4,7-triene (44). To a solution of vinyl ether 13 in S02 at -78 °C was added an excess (3 equiv) of S02C1F. The reaction was instantaneous. The reaction mixture was pour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…It should also be mentioned that dicyanocobalamin has a 59C0 resonance shielded by 770 ppm compared with cyanocobalamin [lo], an effect assigned to the special shielding property of the cyanide ion. As the 5-hydroxybenzimidazole becomes free, the observed d(N) values resemble those of 1-methylbenzimidazole [19], i.e. -218.0 ppm (N(1)) and -119.…”
Section: L-220mentioning
confidence: 90%
See 1 more Smart Citation
“…It should also be mentioned that dicyanocobalamin has a 59C0 resonance shielded by 770 ppm compared with cyanocobalamin [lo], an effect assigned to the special shielding property of the cyanide ion. As the 5-hydroxybenzimidazole becomes free, the observed d(N) values resemble those of 1-methylbenzimidazole [19], i.e. -218.0 ppm (N(1)) and -119.…”
Section: L-220mentioning
confidence: 90%
“…We found that the following long-range coupling constants are of crucial importance for correct "N-resonance assignments : Table I with other easily assignable resonances are given for all the compounds studied. The differentiation between H-C( 19) and H-C(3) is sometimes prevented because of overlap of these signals with H-C(R4) or H-C(Pr2). In these cases, decoupling experiments between H-C(18) and H-C(19) are very useful.…”
Section: Con T -12mentioning
confidence: 99%
“…The standard one-dimensional CP/MAS pulse sequence" was used. General recording parameters were quadrature detection, 'H 90" pulse duration 5 ps, C P times [8][9][10][11][12][13][14][15] …”
Section: Methodsmentioning
confidence: 99%
“…Taking into account previously established nitroimine structure of compound V in solution [19], we believe that compounds I-IV and VI have a similar structure. Nevertheless, rigorous conclusion on the structure of nitroamino-1,2,4-triazoles in solution requires 15 N NMR spectra to be recorded for both compounds I-III and VI and their N-methyl derivatives [30,31]. No rigorous experimental proof for the existence of such tautomerism has been reported so far.…”
Section: IVmentioning
confidence: 99%